A layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material and its application
By adopting layered-spinel composite phase single crystal lithium-rich manganese-based cathode materials and their preparation methods, the deficiencies of lithium-rich manganese-based cathode materials in terms of cycle stability and compaction density are solved, and efficient synthesis of materials and Excellent electrochemical performance.
Patent Information
- Application Number
- CN202211243362.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-11
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-10-11
Smart Images

Figure CN115395007B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium-ion batteries, and in particular relates to a layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material and an application thereof. Background Art
[0002] Lower cost and higher energy density are the technical directions that lithium-ion batteries continue to pursue, among which the positive electrode material is the key factor affecting battery characteristics. In recent years, lithium-rich manganese-based positive electrode materials have become increasingly valued due to their high specific capacity (>250mAh / g), high average voltage (>3.6V), and low cost (high manganese and low cobalt), and are considered to be the most promising next-generation lithium battery positive electrode materials. Despite this, lithium-rich manganese-based materials still have some shortcomings, such as poor cycle stability and low compaction density. Researchers can significantly improve the structural stability of lithium-rich materials through doping, coating and other technologies, thereby greatly improving their cycle performance, but their compaction density has not been improved.
[0003] Traditional lithium-rich manganese-based materials are usually polycrystalline with primary particles agglomerated into secondary spherical particles. The natural stacking of particles inevitably produces voids, which reduces the compaction density. On the other hand, it also increases the specific surface area, promotes gas production and microcracks during the cycle, aggravates the side reactions with the electrolyte, and further deteriorates the electrochemical performance. In the whole battery manufacturing process, the low compaction density will also affect the battery. These shortcomings have become the main obstacles to its commercial application.
[0004] Single crystal materials have good crystallinity, high mechanical strength, and small surface area. They can inhibit the formation of surface microcracks on material particles during the cycle, side reactions with electrolytes, and cyclic gas production. They are a feasible method to extend the cycle life of materials and can also significantly improve the compaction density of materials.
[0005] Single crystal particles can be obtained by introducing a sintering aid during the sintering process of the material. For example, Chinese patent CN107834063B uses potassium chloride as an additive to obtain a single crystal one-dimensional lithium-rich material. However, this method uses a large amount of additives (molar ratio to lithium source 5 to 20:1) and the process is complex (washing is required), which makes it difficult to achieve batch expansion due to low efficiency.
[0006] Yang and his team used wet ball milling combined with solid-phase reaction method to obtain single-crystal lithium-rich manganese-based positive electrode materials with different component ratios (Journal of Alloys and Compounds 770 (2019) 490-499), but the wet ball milling method they used requires the use of acetone reagent and the sample is prone to agglomeration.
[0007] Chinese patent application CN108598457A discloses a method for preparing a single-crystal lithium-rich manganese-based positive electrode material, in which single-crystal particles are obtained by pre-burning a precursor and using a small amount of a boron-containing additive (0-2%), but steps such as pre-burning and crushing of the precursor are added, and the process is relatively complicated.
[0008] Chinese patent application CN114094080A discloses a single crystal lithium-rich layered-spinel composite positive electrode material and a preparation method thereof. After pickling and heat treatment, an oxide coating layer is formed on the surface. The introduction of the spinel phase is beneficial to improving the rate performance of the material and overcoming the problems of poor lithium ion diffusion of single crystal materials. However, it needs to be pickled, and there are also problems such as complex process and large amount of additives.
[0009] Therefore, researchers need to continue to study the composition, structure and preparation process of lithium-rich layered-spinel materials to improve their comprehensive performance and successfully realize the industrialization of materials.
[0010] In view of this, the present invention aims to overcome the above technical defects and proposes a layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Summary of the invention
[0011] The present invention provides a layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material, the chemical formula of the lithium-rich manganese-based positive electrode material is Li x Mn a Ni b Co c B d M e O 2-δ , wherein M is at least one element selected from Al, Ti, W, Mo, La, V, and Y, 1<x≤1.3, 0.3≤a≤0.8, 0.1≤b≤0.5, 0≤c≤0.3, 0<d≤0.055, 0<e≤0.02, e:d=0.01~0.45:1, -0.15<δ<0.15, and the positive electrode material contains both a layered phase and a spinel phase.
[0012] Among them, preferably, in the components of the lithium-rich manganese-based positive electrode material, the content of M and the content of B meet the ratio of e:d=0.1 to 0.4:1.
[0013] Wherein, the layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material is a single crystal particle with a particle size of 0.5-10 μm, preferably 2-6 μm.
[0014] Among them, the spinel phase of the layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material is formed in situ and is uniformly distributed with the layered phase. In the XRD spectrum, it has obvious spinel phase characteristic peaks such as (311) and (400) and layered phase characteristic peaks such as (101) and (104) as well as Li2MnO3 phase characteristic peaks; preferably, in the XRD spectrum of the positive electrode material, the intensity ratio of the spinel phase (311) peak to the layered phase (101) peak is 0.5:1 to 0.8:1; more preferably, the intensity ratio of the spinel phase (311) peak to the layered phase (101) peak is 0.7:1 to 0.8:1.
[0015] The present invention also provides a method for preparing the layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material, comprising the following steps:
[0016] (1) According to the chemical formula, a soluble metal salt solution prepared by a soluble salt containing a manganese element, a soluble salt containing a nickel element, and a soluble salt containing a cobalt element, a precipitant, a buffer, and water are used to prepare a lithium-rich manganese-based material precursor through a precipitation reaction at a certain system temperature;
[0017] (2) according to its chemical formula, a certain amount of boron-containing compound, an additive Z containing the M element, and a lithium source compound are added to the lithium-rich manganese-based material precursor described in step (1), and the mixture is mixed uniformly to obtain a lithium-rich manganese-based precursor mixture;
[0018] (3) The mixture obtained in step (2) is subjected to high temperature sintering to obtain a layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material.
[0019] Wherein, in the step (1), the soluble metal salt includes one or more of sulfate, acetate, and nitrate; the precipitant is one or more of sodium hydroxide and potassium hydroxide; the buffer includes one or more of ammonia water, oxalic acid, citric acid, and ethylenediaminetetraacetic acid; the reaction temperature is 40-70° C., and the reaction time is 10-30 hours.
[0020] Wherein, in the step (2), the boron-containing compound includes one or more of boric acid, lithium metaborate, diboron trioxide, lithium tetraborate, and lithium tetrafluoroborate; preferably boric acid or diboron trioxide. The auxiliary agent Z is one or more selected from lithium titanate, lithium tungstate, lithium molybdate, lithium vanadate, aluminum oxide, titanium oxide, tungsten oxide, molybdenum oxide, vanadium oxide, lanthanum oxide, and yttrium oxide; preferably, the auxiliary agent Z is one or more selected from lithium titanate, lithium tungstate, lithium molybdate, lithium vanadate, titanium oxide, tungsten oxide, molybdenum oxide, and vanadium oxide; more preferably, it is one or more selected from lithium titanate, lithium tungstate, titanium oxide, and tungsten oxide.
[0021] Wherein, in step (2), the lithium source compound is at least one of lithium acetate, lithium carbonate, lithium nitrate, lithium chloride and lithium hydroxide, and the molar ratio of the added amount of the lithium source in terms of lithium to the lithium-rich manganese-based precursor is 1:1 to 1.3:1.
[0022] Wherein, in the step (3), the atmosphere of the high-temperature sintering is an oxygen-containing atmosphere, and the sintering conditions are heating to 300-700°C at a heating rate of 1-10°C / min and keeping warm for 3-7h; then heating to 800-1000°C at a heating rate of 1-10°C / min and keeping warm for 10-20h.
[0023] The present invention also provides a single crystal lithium-rich manganese-based positive electrode material prepared by the method for preparing the layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material.
[0024] The present invention also provides a lithium-ion battery, which comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the above-mentioned layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material.
[0025] The beneficial effects of the present invention are:
[0026] (1) The present invention creatively uses the synergistic effect of composite additives, not only using their fluxing properties to achieve the synthesis of single crystals, but also successfully doping a variety of beneficial elements, while improving the compaction density and cycle stability of the material. The compaction density of the single crystal lithium-rich manganese-based positive electrode material can reach 3.5g / cm 3 When the single crystal lithium-rich manganese-based positive electrode material of the present invention is used as the positive electrode active material of a lithium-ion battery, at 25° C. and a cut-off voltage of 2-4.8V, the capacity retention rate can reach more than 99% after 100 cycles at a rate of 1C (1C=200mA / g), and the capacity retention rate can reach more than 96% after 200 cycles.
[0027] (2) The present invention forms a spinel-layered composite structure in situ, and the spinel can effectively improve the lithium ion transmission efficiency and the rate performance of the material. When the single crystal lithium-rich manganese-based positive electrode material of the present invention is used as the positive electrode active material of a lithium-ion battery, the first discharge capacity at a rate of 3C (1C = 200mA / g) is more than 150mAh / g at 25°C and a cut-off voltage of 2-4.8V, and the first discharge capacity at a rate of 5C (1C = 200mA / g) is more than 130mAh / g, which is significantly higher than the rate performance of the synthesized comparative sample material.
[0028] (3) The present invention is used to prepare and synthesize a single-crystal lithium-rich manganese-based positive electrode material with a particle size between 0.5 and 10 μm. The particles are uniform and the size is controllable. At the same time, the elements are evenly distributed.
[0029] (4) The present invention adopts a method of adding a composite auxiliary agent, which uses a small amount of auxiliary agent and does not require washing. The process is simple and efficient, and is easy to scale up and industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the single crystal lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention.
[0031] Figure 2 This is the XRD diagram of the single crystal lithium-rich manganese-based positive electrode material prepared in Example 1 of the present invention.
[0032] Figure 3 This is a SEM image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 of the present invention.
[0033] Figure 4 This is the XRD diagram of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 of the present invention.
[0034] Figure 5 This is a SEM image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 2 of the present invention.
[0035] Figure 6 This is the XRD diagram of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 2 of the present invention.
[0036] Figure 7 This is a SEM image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 3 of the present invention.
[0037] Figure 8 This is the XRD diagram of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 3 of the present invention.
[0038] Fig. 9 This is a SEM image of the single crystal lithium-rich manganese-based positive electrode material prepared in Example 2 of the present invention.
[0039] Fig.10 This is a SEM image of the single crystal lithium-rich manganese-based positive electrode material prepared in Example 3 of the present invention.
[0040] Fig.11 This is a SEM image of the single crystal lithium-rich manganese-based positive electrode material prepared in Example 4 of the present invention.
[0041] Fig.12 This is a SEM image of the single crystal lithium-rich manganese-based positive electrode material prepared in Example 5 of the present invention.
[0042] Fig.13 It is a first charge and discharge curve diagram of the lithium-rich manganese-based positive electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention.
[0043] Fig.14This is a cycle performance diagram of the lithium-rich manganese-based positive electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention.
[0044] Fig.15 This is a rate performance diagram of the lithium-rich manganese-based positive electrode materials prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0045] The present invention will be described in further detail below in conjunction with specific embodiments. However, it should be understood that these embodiments are only for illustration and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims of the present application.
[0046] Example 1
[0047] Single crystal Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.04 W 0.01 O 2.09 The lithium-rich manganese-based material, the preparation method thereof comprises the following steps:
[0048] Manganese sulfate monohydrate, nickel sulfate hexahydrate and cobalt sulfate heptahydrate are dissolved in deionized water according to a stoichiometric ratio of 55:15:10 to prepare a 2 mol / L mixed salt solution; sodium hydroxide is selected as a precipitant to prepare a precipitant solution, wherein an appropriate amount of ammonia water is added as a buffer, and the concentration of sodium hydroxide in the precipitant solution is 2 mol / L, and the concentration of ammonia water is 4 mol / L; 20% volume ratio of deionized water of the reaction kettle is added into the reaction kettle as a reaction base liquid, and the above two solutions are slowly added under high-speed stirring, and the pH value is 10.3, the temperature is 50°C, and the reaction is carried out for 12 hours, and then filtered, washed and dried to obtain a precursor material.
[0049] The obtained precursor material, lithium carbonate, auxiliary lithium tungstate and auxiliary boric acid are mixed uniformly in a high-speed mixer at a molar ratio of 1:0.75:0.01:0.04 (W / B=0.25, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), and the mixture is placed in an air atmosphere of a muffle furnace, and the temperature is increased to 550°C at a heating rate of 6°C / min. After keeping the temperature for 5 hours, the temperature is continuously increased to 900°C at the same heating rate, and the temperature is kept for 10 hours. After cooling to room temperature, a single crystal lithium-rich manganese-based positive electrode material is obtained.
[0050] The scanning electron microscope was used to test Example 1. Figure 1From the scanning electron microscope photo, it can be seen that the lithium-rich manganese-based positive electrode material obtained in Example 1 has a single crystal morphology, uniform particle distribution, uniform size, smooth surface, and a particle size D50 of 2.5 μm. From the EDS results, it can be seen that the single crystal lithium-rich manganese-based positive electrode material obtained in Example 1 has uniform distribution of elements. Figure 2 The X-ray diffraction pattern shows that the material contains both spinel phase and layered phase.
[0051] Preparation of lithium-ion battery: The single crystal lithium-rich manganese-based positive electrode material prepared in Example 1, acetylene black, polyvinylidene fluoride and N-methylpyrrolidone are mixed to form a slurry, which is evenly coated on the surface of an aluminum foil to obtain a positive electrode plate. A lithium plate is used as a negative electrode plate, and a 1 mol / L lithium hexafluorophosphate ethylene carbonate (EC) and dimethyl carbonate (DMC) solution (the volume ratio of EC to DMC is 1:1) is used as an electrolyte. The batteries are assembled in a glove box to obtain a lithium-ion battery.
[0052] The electrochemical performance of the lithium ion battery of Example 1 was tested using an electrochemical tester at a test temperature of 25° C. At a current density of 0.1C (1C=200mAh / g) and a charging voltage range of 4.8 to 2V, the initial charge and discharge performance of the battery was tested. Fig.13 , compared with the first charge and discharge curves of Comparative Examples 1, 2 and 3, it is obvious that the first discharge capacity of Example 1 is larger and the first efficiency is higher. The cycle performance of the battery is tested at a 1C rate. Fig.14 , compared with the cycle curves of Comparative Examples 1, 2 and 3, the cycle curve of the embodiment is more gentle, with no obvious change trend. The rate performance of the battery was tested at 0.1C, 0.2C, 0.5C, 1C, 3C and 5C rates. Fig.15 , compared with the rate performance curves of Comparative Examples 1, 2 and 3, the performance of Example 1 at high rates of 3C and 5C is significantly better than that of the three comparative examples. The detailed results are shown in Table 1.
[0053] Comparative Example 1
[0054] Prepared Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 O2 lithium-rich manganese-based material, the preparation method thereof comprises the following steps:
[0055] The precursor obtained in Example 1 and lithium carbonate were mixed uniformly in a high-speed mixer at a molar ratio of 1:0.75 (Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), and the mixture was placed in an air atmosphere of a muffle furnace, and the temperature was increased to 550°C at a heating rate of 6°C / min, and then the temperature was kept at this rate for 5 hours and then continued to be increased to 900°C at the same heating rate, and the temperature was kept at this rate for 10 hours. After cooling to room temperature, a lithium-rich manganese-based positive electrode material was obtained.
[0056] The comparative example 1 was tested by scanning electron microscope. Figure 3 From the scanning electron microscope photograph, it can be seen that the lithium-rich manganese-based positive electrode material obtained in Comparative Example 1 has a polycrystalline morphology, the particles are obviously agglomerated into spheres, and the particle size is at the nanometer level. Figure 4 The X-ray diffraction pattern shows that the material contains only a lamellar phase.
[0057] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 1 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Comparative Example 1 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0058] Comparative Example 2
[0059] Prepared Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.04 O 2.06 A lithium-rich manganese-based material, the preparation method of which comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate and auxiliary agent boric acid in a high-speed mixer at a molar ratio of 1:0.75:0.04 (Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 900°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a lithium-rich manganese-based positive electrode material.
[0060] The comparative example 2 was tested by scanning electron microscope. Figure 5 From the scanning electron microscope photograph, it can be seen that the lithium-rich manganese-based positive electrode material obtained in Comparative Example 2 has a single crystal morphology and dispersed particles, but the particle size is too large (>15μm), the size distribution is uneven, and there are fine particles on the particle surface. Figure 6 From the X-ray diffraction pattern, it can be seen that the diffraction peaks of the material can be matched to the layered phase.
[0061] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 2 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Comparative Example 2 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0062] Comparative Example 3
[0063] Prepared Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 W 0.01 O 2.03 A lithium-rich manganese-based material, the preparation method of which comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate and the auxiliary agent lithium tungstate in a high-speed mixer at a molar ratio of 1:0.75:0.01 (Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 900°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a lithium-rich manganese-based positive electrode material.
[0064] The comparative example 3 was tested by scanning electron microscope. Figure 7 From the scanning electron microscope photograph, it can be seen that the lithium-rich manganese-based positive electrode material obtained in Comparative Example 3 has a polycrystalline morphology, the particles are obviously agglomerated into spheres, and the particle size is at the nanometer level. Figure 8 From the X-ray diffraction pattern, it can be seen that after comparison with the PDF card, the material only contains lamellar phase.
[0065] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 3 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Comparative Example 3 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0066] Comparative Example 4
[0067] Prepared Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.06 W 0.01 O 2.12A lithium-rich manganese-based material, and a preparation method thereof comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate, and auxiliary boric acid and auxiliary lithium tungstate in a high-speed mixer at a molar ratio of 1:0.75:0.06:0.01 (W / B=0.167, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 900°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0068] Comparative Example 4 was tested using a scanning electron microscope. Although the lithium-rich manganese-based positive electrode material obtained in Comparative Example 4 had a single crystal morphology, the particle size was too large (>20 μm) and the size distribution was uneven.
[0069] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 4 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Comparative Example 4 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0070] Comparative Example 5
[0071] Polycrystalline Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.03 W 0.03 O 2.135 A lithium-rich manganese-based material, and a preparation method thereof comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate, and auxiliary boric acid and auxiliary lithium tungstate in a high-speed mixer at a molar ratio of 1:0.75:0.03:0.03 (W / B=1, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 900°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0072] Comparative Example 5 was tested using a scanning electron microscope. The lithium-rich manganese-based positive electrode material obtained in Comparative Example 5 had a polycrystalline morphology, the particles were obviously agglomerated into spheres, and the particle size was at the nanometer level.
[0073] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 5 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Comparative Example 5 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0074] Comparative Example 6
[0075] Polycrystalline Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.04 W 0.01 O 2.09 A lithium-rich manganese-based material, and a preparation method thereof comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate, and auxiliary boric acid and auxiliary lithium tungstate in a high-speed mixer at a molar ratio of 1:0.75:0.04:0.01 (W / B=0.25, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 700°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a lithium-rich manganese-based positive electrode material.
[0076] The comparative example 6 was tested by scanning electron microscopy. The lithium-rich manganese-based positive electrode material obtained in the comparative example 6 had a polycrystalline morphology, the particles were obviously agglomerated into spheres, and the particle size was at the nanometer level.
[0077] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 6 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Comparative Example 6 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0078] Comparative Example 7
[0079] Prepared Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.04 W 0.01 O 2.09 A lithium-rich manganese-based material, and a preparation method thereof comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate, and auxiliary boric acid and auxiliary lithium tungstate in a high-speed mixer at a molar ratio of 1:0.75:0.04:0.01 (W / B=0.25, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 1100°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0080] Comparative Example 7 was tested using a scanning electron microscope. Although the lithium-rich manganese-based positive electrode material obtained in Comparative Example 7 had a single crystal morphology, the particle size was too large (>20 μm), the size distribution was uneven, and fine particles existed.
[0081] The lithium-rich manganese-based positive electrode material prepared in Comparative Example 7 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Comparative Example 7 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0082] Example 2
[0083] Single crystal Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.04 Ti 0.015 O 2.09 A lithium-rich manganese-based material, and a preparation method thereof comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate, and auxiliary boric acid and auxiliary lithium titanate in a high-speed mixer in a molar ratio of 1:0.75:0.04:0.015 (Ti / B=0.375, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 900°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0084] The scanning electron microscope was used to test Example 2. Fig. 9 From the scanning electron microscope photograph, it can be seen that the lithium-rich manganese-based positive electrode material obtained in Example 2 has a single crystal morphology, uniform particle distribution, uniform size, smooth surface, and a particle size D50 of 0.6 μm.
[0085] The lithium-rich manganese-based positive electrode material prepared in Example 2 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Example 2 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0086] Example 3
[0087] Single crystal Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.035 Ti 0.015 O 2.0825A lithium-rich manganese-based material, and a preparation method thereof comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate, and auxiliary boric acid and auxiliary lithium titanate in a high-speed mixer in a molar ratio of 1:0.75:0.035:0.015 (Ti / B=0.429, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 900°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0088] The scanning electron microscope was used to test Example 3. Fig.10 From the scanning electron microscope photograph, it can be seen that the lithium-rich manganese-based positive electrode material obtained in Example 6 has a single crystal morphology, uniform particle distribution, uniform size, and a smooth surface. The particle size D50 is 0.2 μm.
[0089] The lithium-rich manganese-based positive electrode material prepared in Example 3 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Example 3 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0090] Example 4
[0091] Single crystal Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.04 Mo 0.01 O 2.09 A lithium-rich manganese-based material, and a preparation method thereof comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate, and auxiliary boric acid and auxiliary lithium molybdate in a high-speed mixer at a molar ratio of 1:0.75:0.04:0.01 (Mo / B=0.25, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 900°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0092] The scanning electron microscope was used to test Example 4. Fig.11 From the scanning electron microscope photograph, it can be seen that the lithium-rich manganese-based positive electrode material obtained in Example 4 has a single crystal morphology, uniform particle distribution, uniform size, and a smooth surface. The particle size D50 is 2.16 μm.
[0093] The lithium-rich manganese-based positive electrode material prepared in Example 4 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Example 4 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0094] Example 5
[0095] Single crystal Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.04 V 0.01 O 2.085 A lithium-rich manganese-based material, and a preparation method thereof comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate, and auxiliary boric acid and auxiliary lithium vanadate in a high-speed mixer at a molar ratio of 1:0.75:0.04:0.01 (V / B=0.25, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in an air atmosphere of a muffle furnace, heating the mixture to 550°C at a heating rate of 6°C / min, keeping the temperature for 5 hours, and then continuing to heat the mixture to 900°C at the same heating rate, keeping the temperature for 10 hours, and cooling the mixture to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0096] The scanning electron microscope was used to test Example 5. Fig.12 From the scanning electron microscope photograph, it can be seen that the lithium-rich manganese-based positive electrode material obtained in Example 5 has a single crystal morphology, uniform particle distribution, uniform size, and a smooth surface. The particle size D50 is 2.24 μm.
[0097] The lithium-rich manganese-based positive electrode material prepared in Example 5 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Example 5 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0098] Example 6
[0099] Single crystal Li 1.2 Mn 0.55 Ni 0.15 Co 0.1 B 0.04 Al 0.01 O 2.075A lithium-rich manganese-based material, the preparation method of which comprises the following steps: mixing the precursor obtained in Example 1, lithium carbonate, and auxiliary boric acid and auxiliary aluminum oxide in a high-speed mixer at a molar ratio of 1:0.75:0.04:0.01 (Al / B=0.25, Li / TM=1.2:0.8, TM is the total molar amount of transition metal ions), placing the mixture in a muffle furnace air atmosphere, heating it to 550°C at a heating rate of 6°C / min, keeping it warm for 5 hours, and then continuing to heat it to 900°C at the same heating rate, keeping it warm for 10 hours, and cooling it to room temperature to obtain a single crystal lithium-rich manganese-based positive electrode material.
[0100] The scanning electron microscope was used to test Example 6, and the lithium-rich manganese-based positive electrode material obtained in Example 6 had a single crystal morphology, uniform particle distribution, uniform size, and a smooth surface. The particle size D50 was 2.5 μm.
[0101] The lithium-rich manganese-based positive electrode material prepared in Example 5 was used to prepare a lithium-ion battery in the same manner as in Example 1. The electrochemical performance of the lithium-ion battery of Example 5 was tested using an electrochemical tester under the same conditions as in Example 1. The results are shown in Table 1.
[0102]
[0103] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material, the chemical formula of the lithium-rich manganese-based positive electrode material is Li x Mn a Ni b Co c B d M e O 2-δ , wherein M is at least one element selected from W, Mo, La, and V, 1<x≤1.3, 0.3≤a≤0.8, 0.1≤b≤0.5, 0≤c≤0.3, 0<d≤0.055, 0<e≤0.02, e:d=0.1~0.45:1, -0.15<δ<0.15, and the positive electrode material contains both a layered phase and a spinel phase; In the XRD spectrum of the positive electrode material, the intensity ratio of the (311) peak of the spinel phase to the (101) peak of the layered phase is 0.5:1 to 0.8:1; in, The layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material is a single crystal particle with a particle size of 0.5-10 μm.
2. The layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material according to claim 1, wherein: In the components of the lithium-rich manganese-based positive electrode material, the content of M and the content of B meet the ratio of e:d=0.1 to 0.4:
1.
3. The layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material according to claim 1, wherein in the XRD spectrum of the positive electrode material, the intensity ratio of the spinel phase (311) peak to the layered phase (101) peak is 0.7:1 to 0.8:
1.
4. The layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material according to claim 1, wherein: The spinel phase of the layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material is formed in situ and is evenly distributed with the layered phase.
5. The method for preparing the layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4, comprising the following steps: (1) According to its general chemical formula, a soluble metal salt solution, a precipitant, a buffer and water are used to prepare a lithium-rich manganese-based precursor by a precipitation reaction at a certain system temperature, wherein: The soluble metal salt solution includes a soluble salt containing manganese, a soluble salt containing nickel, and a soluble salt containing cobalt; the precipitant is one or more of sodium hydroxide and potassium hydroxide; (2) according to its chemical formula, a certain amount of boron-containing compound, an additive Z containing the M element, and a lithium source compound are added to the lithium-rich manganese-based material precursor described in step (1), and the mixture is mixed uniformly to obtain a lithium-rich manganese-based precursor mixture; (3) The mixture obtained in step (2) is subjected to high temperature sintering to obtain a layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material.
6. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 5, wherein: In the step (1), the soluble salt containing manganese, the soluble salt containing nickel, and the soluble salt containing cobalt include one or more of sulfates, acetates, and nitrates of the corresponding elements; the buffer includes one or more of ammonia water, oxalic acid, citric acid, and ethylenediaminetetraacetic acid; the reaction temperature is 40-70° C., and the reaction time is 10-30 hours.
7. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 5, wherein: in, In the step (2), the auxiliary agent Z is one or more selected from lithium titanate, lithium tungstate, lithium molybdate, lithium vanadate, aluminum oxide, titanium oxide, tungsten oxide, molybdenum oxide, vanadium oxide, lanthanum oxide, and yttrium oxide.
8. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 5, wherein: The molar ratio of the amount of the lithium source added in terms of lithium to the lithium-rich manganese-based precursor is 1:1 to 1.3:
1.
9. A lithium-ion battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the layered-spinel composite phase single crystal lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4.
Citation Information
Patent Citations
A single-crystal one-dimensional lithium-rich manganese-based cathode material and its preparation method
CN107834063B
Single crystal lithium-rich manganese-based anode material, preparation method thereof, lithium ion battery
CN108598457A
Single crystal type lithium-rich layered-spinel composite positive electrode material and preparation method thereof
CN114094080A
Lithium-enriched manganese-based material precursor as well as preparation method, lithium-enriched manganese-based anode material and preparation method thereof, lithium battery
CN108557905A
Preparation and application of single crystal-like lithium-rich layered oxide material
CN109778301A